Dexamethasone treatment in vivo counteracts the functional pancreatic islet alterations caused by malnourishment in rats - Giozzet, Vanessa A. G.; Rafacho, Alex; Boschero, Antonio C.; Cameiro, Everardo M.; Bosqueiro, José Roberto [UNESP] (W B Saunders Co-elsevier Inc, 2008)
The effects of dexamethasone (Dex) on the metabolic parameters, peripheral insulin, and glucose sensitivity in vivo as well as on islet function ex vivo of rats submitted to low-protein diet were analyzed. Dexamethasone (1.0 mg/kg body weight) was administered intraperitoneally daily to adult Wistar rats fed on a normal-protein diet or low-protein diet (LPD) for 5 days, whereas control rats fed on a normal-protein diet or low-protein diet (LP) received saline alone. At the end of the experimental period, LP rats showed a significant reduction in serum insulin, total serum protein, and serum albumin levels compared with rats fed on a normal-protein diet (P < .05). All these parameters tended to be normalized in LPD rats (P < .05); furthermore, these rats exhibited increased serum glucose and nonesterified fatty acid levels compared with LP rats (P < .05). Rats submitted to the low-protein diet demonstrated normal peripheral glucose sensitivity and improved peripheral insulin sensitivity, which was reversed by Dex treatment. A reduced area of islets from LP rats was partially recovered in LPD rats (P < .05). At 16.7 mmol/L glucose, insulin secretion from LPD islets was also partially recovered and was significantly higher than that from LP islets (P < .05). In conclusion, induction of insulin resistance by Dex treatment reverses most of the metabolic alterations in rats submitted to a low-protein diet. In addition, several islet functions were also improved by Dex, confirming the plasticity of pancreatic islets in adverse conditions. (C) 2008 Elsevier B.V. All rights reserved.